MEDIA PEMBELAJARAN BERMAIN PERAN PHYGITAL UNTUK ANAK USIA DINI DALAM MENGENAL PROFESI PILOT: MEDIA PEMBELAJARAN BERMAIN PERAN PHYGITAL UNTUK ANAK USIA DINI DALAM MENGENAL PROFESI PILOT - Devanny Gumulya (Ide dan Dialog Desain Indonesia (Idealog), 2025)
Abstract : Early childhood education is essential as it lays the foundation for children's long-term learning. Therefore, developing appropriate and high-quality learning materials is crucial for their growth. The Phygital learning kit is a set of learning materials that integrates both physical and digital elements to enhance learning through play. The study utilizes a qualitative research approach, specifically employing the research through design approach with ADDIE framework, which is an acronym denoting the sequential stages of Analyze, Design, Develop, Implement, and Evaluate. This instructional design methodology is often used in the creation of instructional materials. The study's findings highlight key factors essential for developing Phygital Pretend Play Learning Kit. First, incorporating materials suited to children's age and capabilities. Additionally, the kit needs to have self-paced learning feature that allows children to explore and acquire knowledge independently, promoting autonomy and self-regulation. Third there should be personalization options to further enhance the learning experience by catering to individual needs, preferences, and learning styles. The integration of gamification elements such as levels, rewards, and challenges to boost motivation and sustain long-term participation. Lastly, the use of multi-sensory elements, including tactile, auditory, and visual stimuli, enriches the educational experience and supports holistic development. This study contributes valuable insights to early childhood education by informing the essential key factors for developing phygital learning kit. Keywords: Early Childhood Education, Phygital Pretend Play Learning Kit, Pilot Occupation